A Secure and Reliable Routing Protocol for Wireless Mesh Networks - 黄仁俊 萧宇凯 (Shanghai jiao tong da xue xue bao, 2014)
This study proposes an efficient secure routing protocol which considers symmetric and asymmetric links for wireless mesh networks （WMNs）. A wireless mesh network is a group of wireless mesh routers and several kinds of wireless devices （or nodes）. Individual node cooperates by forwarding packets to each other, allowing nodes to communicate beyond the symmetric or asymmetric links. Asymmetric link is a special feature of WMNs because the wireless transmission ranges of different wireless devices may be different. The asymmetric link enhances WMN coverage. Providing security in WMNs has become an important issue over the last few years. Existing research on this topic tends to focus on providing security for routing and data content in the symmetric link. However, most studies overlook the asymmetric link in these networks. This study proposes a novel distributed routing protocol beyond symmetric and asymmetric links, to guarantee the security and high reliability of the established route in a hostile environment, such as WMNs, by avoiding the use of unreliable intermediate nodes. The routes generated by the proposed protocol are shorter than those in prior works. The major objective of the proposed protocol is to allow trustworthy intermediate nodes to participate in the path construction protocol. The mesh clients out of mesh router wireless transmission range may discover a secure route to securely connect to the mesh router for Internet access via the proposed protocol. The proposed protocol enhances wireless mesh network coverage and assures security.